Salmonella Harborage Sites in Infected Poultry That May Contribute to Contamination of Ground Meat - Rimet, Claire-Sophie; Maurer, John J.; Pickler, Larissa; Stabler, Lisa; Johnson, Kasey K.; Berghaus, Roy D.; Villegas, Ana M.; Lee, Margie; França, Monique (Frontiers in Sustainable Food Systems, 2019)
The role of invasive Salmonella in contamination of ground poultry is poorly defined. Salmonella harborage sites were determined in experimentally infected chickens and turkeys. Bioluminescent-tagged Salmonella were used to follow their spread in bone, meat, and skin following infection. Immunohistochemistry and culture were used to localize Salmonella. Chicken neck skin was positive for S. Heidelberg and S. Typhimurium throughout the experimental period, and the bacteria were localized on the stratum corneum of the epidermis and feather follicles. S. Heidelberg and S. Typhimurium were intermittently detected in drumstick muscle of chickens, with Salmonella primarily localized in connective tissues and lymphatics. Twenty percent of the drumstick muscles were culture positive for Salmonella in chickens at 42 days of age. Blood and tibiotarsus bone were culture positive for S. Heidelberg and S. Typhimurium during the first two weeks of infection. Salmonella levels in neck skin and muscle were <102 CFU/g in chickens at 42 days of age. Multiple S. Heidelberg isolates associated with foodborne outbreaks were used to infect chickens and turkeys to determine whether some strains attained high abundance in the muscle of infected birds. No chicken drumsticks or thighs were Salmonella positive by bioluminescence in chickens at 42 days of age (n = 210). In turkeys, all drumstick muscles (n = 132) and tibiotarsus bone (n = 93) were negative for S. Heidelberg. Thirty percent of the breast skins (n = 93) were culture positive for S. Heidelberg when turkey hens were 11 weeks old. S. Heidelberg were primarily localized on the stratum corneum of the epidermis in turkeys. Exclusion of skin from ground poultry products may be the best option for reducing Salmonella contamination in ground chicken and ground turkey.